Engineering efficient hole transport layer Ferrihydrite-MXene on BiVO4 photoanodes for photoelectrochemical water splitting: Work function and conductivity regulated - Bai, Weihao; Zhou, Ye; Peng, Gang; Wang, Jinnan; Li, Aimin; Corvini, Philippe François-Xavier (Applied catalysis. B, Environmental, 2022)
Although great interest is focused on development of semiconductor photoanodes for efficient photoelectrochemical (PEC) water splitting, the pressing bottleneck to address the intrinsic charge transport for enhancement of PEC performance still remains to be resolved. Herein, hole transport layer (Fh-MXene) constructed by doping of MXene (Ti3C2) in Ferrihydrite (Fh) is loaded on BiVO4 photoanode. This novel BiVO4@Fh-MXene photoanode achieves high current density of 4.55 mA cm−2 at 1.23 V versus reversible hydrogen electrode (vs. RHE), exhibiting excellent photostability. From electrochemical analysis and density functional theory calculations, high PEC performance is ascribed to incorporation of Fh-MXene as hole transport layer, enhancing conductivity and water oxidation reaction. Notably, MXene can improve band alignment of BiVO4/Fh-MXene interface by tuning work function, which strengthens the built-in electric field for more efficient hole extraction. This work provides a simple method to design photoanodes with efficient charge transport layers for feasible PEC water splitting application. [Display omitted] •Novel hole transfer layer Fh-MXene loaded on BiVO4 photoanode for PEC water splitting.•MXene tune work function of Fh for strengthening the built-in electric field.•Fh-MXene with high conductivity promote the intrinsic charge transport of photoanode.•Exposure of metal sites and hydrophilic functional groups improve water oxidation.•BiVO4@Fh-MXene photoanode exhibit five times enhanced PEC performance than BiVO4.